A new method for anti‐negative interference of calcium dobesilate in serum creatinine enzymatic analysis. Issue 9 (30th July 2021) - Shen, Hailan; Chen, Kena; Cao, Ju
Abstract: Background: Serum creatinine is a widely used biomarker for evaluating renal function. Sarcosine oxidase enzymatic (SOE) analysis is currently the most widely used method for the detection of creatinine. This method was negatively interfered with by calcium dobesilate, causing pseudo‐reduced results. The aim of this study was to explore a new method to alleviate the negative interference of this drug on creatinine detection. Method: We formulated eight drug concentrations and 12 creatinine concentrations from serum. The SOE method, the new method, and the Jaffe method were used for detection in five systems. Creatinine biases were analyzed under the conditions with or without the interference of calcium dobesilate, at consistent or inconsistent creatinine concentrations. Creatinine concentrations were also analyzed at three medical decision levels (MDLs). Results: Calcium dobesilate had negative interference in creatinine SOE analysis. With the increase in calcium dobesilate concentrations, the negative bias increases. The new BG method showed an anti‐negative interference effect. In the Roche system, the BG method reduced the negative bias from −71.11% to −16.7%. In the Abbott system, bias was reduced from −45.15% to −2.74%. In the Beckman system, the bias was reduced from −65.36% to −7.58%. In the Siemens system, the bias was reduced from −58.62% to −7.58%. In the Mindray system, the bias was reduced from −36.29% to −6.84%. Conclusion: The new method alleviated the negative interference of calcium dobesilate in creatinine SOE detection. The negative bias could be reduced from −60% or −70% to less than −20%. Abstract : The serum creatinine quantitative method SOE was negatively interfered with by the commonly used drug calcium dobesilate, resulting in lower than the actual value. The new BG reagent laccase was added to prevent the generation of negative interference and make the detection more accurate. Schematic diagram of creatinine detection of the new BG reagent. SOD: sarcosine oxidase. 4‐AAP: 4‐aminophenazone. POD: peroxidase. HTIB: 2, 4, 6‐triiodo‐3‐hydroxybenzoic acid. Qic: quinoneimine chromogen. Calcium dobesilate is a strong reducing agent that consumes H2 O2 during the reaction, resulting in decreased QIC of the final chromatographic substance. Laccase is a strong oxidant that can oxidize calcium dobesilate in advance before H2 O2 is produced so that H2 O2 will not be consumed and negative interference can be avoided.